Anti-Autooxidative and Anti-Photooxidative Effect of Lemon Grass Extracts (Cymbopogon citratus) - Sri Raharjo; Edi Suryanto (Indonesian Food and Nutrition Progress, 2005)
Lemon grass (Cymbopogon citratus) is a traditional food ingredient characterized by its specific and refreshing aroma. This study was intended determine to the effect of lemon grass extract in both autooxidation and photooxidation reaction in model systems. Lemon grass was extracted sequentially with hexane, acetone and ethanol. The antioxidative effects of the extracts were determined by 1,1-diphenyl-2-spicrylhydrazyl (DPPH) scavenging assay, reducing power, β-carotene bleaching method and linoleic acid system. The photooxidation reaction system was consisted of linoleic acid (0,03 M) in methanol containing 100 ppm erythrosine as a sensitizer and the reaction mixture was exposed under 4000 lux fluorescent light for up to 5 hours. Total phenolic content of acetone, hexane and ethanol extracts were 20.38, 7.65, and 4.97 mg/100g, respectively, which was expressed as gallic acid equivalent. The addition of acetone extracts of lemon grass at 200 and 500 ppm in the reaction mixture showed the highest scavenging activity in 1,1-diphenyl-2-spicrylhydrazyl (DPPH) radical, reducing power, and β-carotene bleaching and linoleic acid system.